The impact of student-athlete social identity on psychosocial adjustment during a challenging educational transition. (September 2021) - Parker, Patti C.; Perry, Raymond P.; Coffee, Pete; Chipperfield, Judith G.; Hamm, Jeremy M.; Daniels, Lia M.; Dryden, Robert P.
Abstract: Student-athletes in their first-year transition to university experience many psychological and social stressors as they balance multiple commitments. Our study examined whether a student-athlete social identity affected psychosocial adjustment as students transition to postsecondary, and whether it acted by reducing stress to foster academic adjustment. Student-athletes enrolled in an introductory psychology course at a Canadian university ( n  = 331) were recruited. We assessed whether a relationship existed between student-athlete social identity and key academic indicators of psychosocial adjustment (perceived control, perceived stress, learning-related anxiety); and whether ratings of perceived stress mediated the relationship between student-athlete social identity and psychosocial adjustment measures five-months later. Our findings revealed that student-athlete social identity (a) predicted psychosocial adjustment later in the course; and (b) indirectly enhanced academic control and lowered negative emotions via reductions in perceived stress. This study offers insights on how social identities may promote positive adjustment during the critical transition to university. Highlights: The impact of student-athlete social identity on psychosocial adjustment was tested. Student-athlete social identity influenced adjustment by reductions in stress. Social identities may promote positive adjustment during educational transitions.